DDRE-07. DIPG HARBOUR ALTERATIONS TARGETABLE BY MEK INHIBITORS, WITH ACQUIRED RESISTANCE MECHANISMS OVERCOME BY COMBINATORIAL INHIBITION. (9th November 2020) - Izquierdo, Elisa; Carvalho, Diana; Mackay, Alan; Temelso, Sara; Boult, Jessica K R; Molinari, Valeria; Stubbs, Mark; Grabovska, Yura; Yu, Lu; Choudhary, Jyoti; Depani, Sarita; o'Hare, Patricia; et al.
Abstract: The survival of children with diffuse intrinsic pontine glioma (DIPG) remains dismal, with new treatments desperately needed. In the era of precision medicine, targeted therapies represent an exciting treatment opportunity, yet resistance can rapidly emerge, playing an important role in treatment failure. In a prospective biopsy-stratified clinical trial, we combined detailed molecular profiling (methylation BeadArray, exome, RNAseq, phospho-proteomics) linked to drug screening in newly-established patient-derived models of DIPG in vitro and in vivo . We identified a high degree of in vitro sensitivity to the MEK inhibitor trametinib (GI50 16-50nM) in samples, which harboured genetic alterations targeting the MAPK pathway, including the non-canonical BRAF_ G469V mutation, and those affecting PIK3R1 and NF1 . However, treatment of PDX models and of a patient with trametinib at relapse failed to elicit a significant response. We generated trametinib-resistant clones (62-188-fold, GI50 2.4–5.2µM) in the BRAF _G469V model through continuous drug exposure, and identified acquired mutations in MEK1/2 ( MEK1 _K57N, MEK1 _I141S and MEK2 _I115N) with sustained pathway up-regulation. These cells showed the hallmarks of mesenchymal transition, and expression signatures overlapping with inherently trametinib-insensitive primary patient-derived cells that predicted an observed sensitivity to dasatinib. Combinations of trametinib with dasatinib and the downstream ERK inhibitor ulixertinib showed highly synergistic effects in vitro . These data highlight the MAPK pathway as a therapeutic target in DIPG, and show the importance of parallel resistance modelling and rational combinatorial treatments likely to be required for meaningful clinical translation.